2009
DOI: 10.1021/cr900279a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalation Using d-Block Transition Metals: Fundamental Aspects and Recent Trends

Abstract: Publication date 2010Publication information Chemical Reviews, 110 (2): 576-623Publisher ACS Item record/more information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
394
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(409 citation statements)
references
References 510 publications
13
394
0
2
Order By: Relevance
“…Instead, an aliphatic C-H bond of the mesityl group is activated to produce a six-membered endo-metallacycle. This result, analogous to those reported for cyclopalladation reactions [69,70] can be related to the higher stability of the endo versus exo-metallacycles (the so-called endo effect), which allows to overcome the low tendency to form six-membered rings and to activate a sp 3 C-H bond [18]. For imine 2,6-F 2 C 6 H 3 CH=NCH 2 (2-BrC 6 H 4 ), the fluoro substituents block cyclometallation at the benzylidene ring, and drive the reaction towards formation of a five-membered exo-metallacycle (2g).…”
Section: Six-versus Five-membered and Endo-versus Exo-platinacyclessupporting
confidence: 81%
See 1 more Smart Citation
“…Instead, an aliphatic C-H bond of the mesityl group is activated to produce a six-membered endo-metallacycle. This result, analogous to those reported for cyclopalladation reactions [69,70] can be related to the higher stability of the endo versus exo-metallacycles (the so-called endo effect), which allows to overcome the low tendency to form six-membered rings and to activate a sp 3 C-H bond [18]. For imine 2,6-F 2 C 6 H 3 CH=NCH 2 (2-BrC 6 H 4 ), the fluoro substituents block cyclometallation at the benzylidene ring, and drive the reaction towards formation of a five-membered exo-metallacycle (2g).…”
Section: Six-versus Five-membered and Endo-versus Exo-platinacyclessupporting
confidence: 81%
“…For this reason, the development of new methods for the preparation of cycloplatinated compounds containing N-donor ligands is a pursued goal. In contrast to cyclopalladation reactions for which Pd(OAc) 2 is a very useful precursor leading to formation of a wide variety of palladacycles [18,19], an analogous "universal" starting material is unknown for cycloplatination reactions. Recent reports on cycloplatination reactions proved that cis-[PtCl 2 (dmso) 2 ] is a reasonable metallating agent leading to higher yields and cleaner reactions than the more classical OPEN ACCESS K 2 [PtCl 4 ] starting material [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydrides of platinum group metals have been proven to perform a wide range of σ-bond activation reactions, 18 including the cleavage of C-H bonds, in particular chelate-supported cyclometalation reactions. 19 We have previously used this ability of polyhydrides to prepare several types of phosphorescent osmium(IV) 17 and osmium(II) 8a,20 complexes, by means of sequential σ-bond activation reactions, starting from the d 2 -hexahydride OsH 6 (P i Pr 3 ) 2 . In a consistent manner with the behavior of this hexahydride, we have also observed that the d 4 -pentahydride IrH 5 (P i Pr 3 ) 2 (1) promotes the chelate NHC-supported aryl C-H bond activation of phenyl substituted bis(azolium) salts, to afford different types of dinuclear iridium-NHC complexes containing metalated aryl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as a consequence of the cyclometalation reaction in the square planar complex IrCl(SiNP)(CO), the hydride derivative IrHCl(SiNP-H)(CO), containing two fused five membered IrPNSiC rings, is obtained (Scheme 1A). 3 Despite the large number of cyclometalation reactions involving transition metals, 4 to the best of our knowledge, the oxidative addition of a methyl C-H bond from a diphosphano ligand to rhodium or iridium has been described only for complexes containing the trans spanning ligand 1,3-(CH 2 P Conversely, our preliminary study on the cyclometalation reaction in IrCl(SiNP) (CO) showed that the two phosphorus atoms occupy cis positions and that the six membered IrP 2 N 2 Si ring adopts a boat conformation. 3 Consequently, the flag-pole SiCH 3 is directed toward the iridium(I) centre allowing the oxidative addition of the SiCH 2 -H bond to the metal centre (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%